Combination Drug Therapy for Patients with Intractable Ventricular Tachycardia Associated with Right Ventricular Cardiomyopathy. Issue 1 (17th September 2013) - ERMAKOV, SIMON; HOFFMAYER, KURT S.; GERSTENFELD, EDWARD P.; SCHEINMAN, MELVIN M.
<x xml:space="preserve">Abstract</x> Background Drug therapy for patients with right ventricular (RV) cardiomyopathy refractory to single‐drug therapy and ablation has not been well defined. Methods We reviewed our entire RV cardiomyopathy database (31 patients) and found four patients presenting with ventricular arrhythmias of RV origin refractory to single‐drug therapy. These patients underwent complete evaluation for arrhythmogenic right ventricular cardiomyopathy (ARVC). Results Following the revised 2010 task force criteria, of these four patients, three were diagnosed with ARVC, and one with cardiac sarcoidosis. These patients proved to be refractory to drug monotherapy and either failed or deemed to not be candidates for endocardial ablation. Their arrhythmias were ultimately controlled with combinations of sotalol, flecainide, and mexiletine. Conclusions In our experience, combination drug therapy is an effective treatment strategy for patients with ventricular tachycardia refractory to monotherapy and, in some cases, ablation. In addition, flecainide appears to be safe and effective for those with RV cardiomyopathy without significant left ventricular dysfunction.